Farmers' Preferences for Agri-Environmental Scheme Design: A Choice Experiment Approach - Firoozzare, A; Ghorbani, M; Karbasi, A; Shahnoushi, N; Davari, K (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
Agri-environmental schemes are the main political tool in the world to maintain the relationship between agriculture and environment. The voluntary nature of these schemes is such that farmers’ cooperation is considered the focal point of achieving policy goals. The aim of this article is to investigate farmers’ preferences for agri- environmental schemes of water-related ecosystem services improvement. A choice experiment is used to elicit farmers’ preferences for different attributes of these schemes. Seven attributes of cropping pattern, IPM program, individual or collecti- ve action, scheme length, option of cancelling, monitoring and financial support are investigated. Choice data was gathered through a survey of 376 farmers of Mashhad (northeast of Iran) and modelled by applying conditional logit and random parame- ters logit models. It is concluded that the explanatory power of RPL model compared to CL model is more appropriate. There are heterogeneities among farmers conside- ring IPM, scheme length and level of monitoring and it is probable that the estima- ted parameter sign changes for some farmers. Results, also, show that there is a significant preference for the status quo option. In addition, the option of cancelling the scheme has the most marginal rate of substitution. The second and third places of marginal substitution rates are dedicated to collective action and Implementing proposed cropping pattern attributes. The findings show that credit-based payment for ecosystem services (CB-PES) is appropriate for this scheme in this region.